Rancang Bangun Company Profile Pada Solo Paving By Indo Tegel Berbasis Website Menggunakan Framework Codeigniter - Warasto, Didik; Jalil, Abdul; Silma Bilqista, Nabila (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2025)
In today's digital era, the existence of a company profile website is important for companies to increase the credibility of company information. Solo Paving by Indo Tegel is a company engaged in the production and distribution of paving blocks located in Solo. As an effort to strengthen the company's image, a modern, interactive, and informative company profile website is needed. This research aims to design and build a website-based company profile website for “Solo Paving by Indo Tegel” using the CodeIgniter framework. CodeIgniter was chosen because it is a PHP framework that is lightweight, easy to use, and has complete documentation, making it easier to develop an effective and efficient website. The method used in this research includes several stages. The needs analysis stage is carried out to identify the features needed by the company, such as product information, company profile, and contact form. The result of this research is a responsive, user-friendly, and informative company profile website. This website is expected to help “Solo Paving by Indo Tegel” in strengthening branding and making it easier for customers to get information about the products and services offered by the company.